2016
DOI: 10.3390/s16050705
|View full text |Cite
|
Sign up to set email alerts
|

Xurography as a Rapid Fabrication Alternative for Point-of-Care Devices: Assessment of Passive Micromixers

Abstract: Despite the copious amount of research on the design and operation of micromixers, there are few works regarding manufacture technology aimed at implementation beyond academic environments. This work evaluates the viability of xurography as a rapid fabrication tool for the development of ultra-low cost microfluidic technology for extreme Point-of-Care (POC) micromixing devices. By eschewing photolithographic processes and the bulkiness of pumping and enclosure systems for rapid fabrication and passively driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 44 publications
(55 reference statements)
0
39
0
Order By: Relevance
“…In comparison with the digital cutting-based xurography approach, 25 which has been demonstrated to be powerful in creating 3D microuidic devices with various polymeric materials (e.g., micromixers and micromixing arrays), 26,27 the cutand-paste fabrication of kPADs promises a bench-top, instrumentation-free method to make disposable, paper-based devices for on-site or in-eld applications (vide infra). It should be noted that the size, shape, and number of hydrophobic discs (reaction zones) can be exibly altered to meet any practical demands, i.e., the multiplicity and throughput can be adjusted as needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the digital cutting-based xurography approach, 25 which has been demonstrated to be powerful in creating 3D microuidic devices with various polymeric materials (e.g., micromixers and micromixing arrays), 26,27 the cutand-paste fabrication of kPADs promises a bench-top, instrumentation-free method to make disposable, paper-based devices for on-site or in-eld applications (vide infra). It should be noted that the size, shape, and number of hydrophobic discs (reaction zones) can be exibly altered to meet any practical demands, i.e., the multiplicity and throughput can be adjusted as needed.…”
Section: Resultsmentioning
confidence: 99%
“…25 which has recently shown great advantages in creating PVC micromixers and micro-mixing arrays. 26,27 Inspired by the ancient papercutting art (kirigami), 28 we introduce herein a cut-and-paste protocol to fabricate 3D mPADs (namely kPADs) that are suitable for on-site quantitative assay applications. The novelty of our approach is beyond the cutting aspect that has been reported previously, 29,30 rather, on the modication of the pre-cut paper substrate to be superhydrophobic and the reassembly with the untreated, hydrophilic reaction "discs" or "channels" with a chemically inert adhesive spray to prepare the kPADs.…”
Section: Introductionmentioning
confidence: 99%
“…Martínez-López and co-workers demonstrate the low-cost microfabrication approach called xurography—essentially a CNC knife plotter—as a rapid fabrication method for asymmetric split and recombine micromixing devices [ 33 ]. The team demonstrated that the technique resulted in structures with less than 8% absolute dimensional error.…”
Section: New Methods and Techniques For Flow Control And Mixingmentioning
confidence: 99%
“…While some of these methodologies were originally conceived solely for producing one or few samples within some surface or structural quality limitations, now it is possible to find cases where these techniques have evolved into the production of components that could not be made otherwise [ 9 ]. The incorporation of rapid fabrication technology for microfluidic devices is a growing trend among researchers, but it has not yet been fully developed [ 10 ]. 3D printing has raised much awareness among academics and media because it allows devices to be manufactured on-demand with ease and quickness for medical applications [ 11 ] of microfluidic devices [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address these restrictions in the deployment of a particular type of microfluidic device (SAR) micromixer, we have recently developed a methodology to produce single devices from scratch to testing without the requirement of ancillary laboratory equipment [ 10 , 45 ]. Combining xurography and lamination offered promissing advantages over conventional manufacture such as flexibility, short cycle times, and low-cost.…”
Section: Introductionmentioning
confidence: 99%